2018
DOI: 10.1093/cercor/bhy198
|View full text |Cite
|
Sign up to set email alerts
|

KCC2 Regulates Dendritic Spine Formation in a Brain-Region Specific and BDNF Dependent Manner

Abstract: KCC2 is the major chloride extruder in neurons. The spatiotemporal regulation of KCC2 expression orchestrates the developmental shift towards inhibitory GABAergic drive and the formation of glutamatergic synapses. Whether KCC2’s role in synapse formation is similar in different brain regions is unknown. First, we found that KCC2 subcellular localization, but not overall KCC2 expression levels, differed between cortex and hippocampus during the first postnatal week. We performed site-specific in utero electropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 54 publications
4
40
2
Order By: Relevance
“…This was demonstrated by immunoblotting with N-and Cterminal antibodies and suggests that either the truncated form of KCC2 protein is unstable and does not accumulate, or that the altered gene sequence results in premature transcriptional or translational termination. This is contrary to previous work (9,10), and likely represents the differences associated with endogenous versus overexpression systems. We were not able to completely ablate KCC2 expression in vitro or in vivo under these experimental conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated by immunoblotting with N-and Cterminal antibodies and suggests that either the truncated form of KCC2 protein is unstable and does not accumulate, or that the altered gene sequence results in premature transcriptional or translational termination. This is contrary to previous work (9,10), and likely represents the differences associated with endogenous versus overexpression systems. We were not able to completely ablate KCC2 expression in vitro or in vivo under these experimental conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study demonstrated that the genetic removal of KCC2 during neuronal migration induces the apoptosis of embryonic neocortical projection neurons (23). Yet, the functional consequences of KCC2 removal during postnatal neuronal development have not been investigated and are of great interest as a number of studies have suggested that KCC2 plays a transport independent role in determining spine morphology (9,10). These studies used overexpression of a KCC2 construct devoid of its cytoplasmic tail (residues Q911-Q1096) or a DNA construct modified with a GFP reporter which may act to stabilize this truncated form of KCC2 (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…5, panels I–L). Similar to previously published results 25 , at both P10 (Fig. 5I, arrow) and P17 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…The mechanisms governing spine formation and plasticity are poorly understood (for review, see Yoshihara et al, 2009; Murakoshi and Yasuda, 2012), and are developmental age- and brain region-specific, making it difficult to directly compare these previous studies with our own. For example the major chloride extruder in neurons, KCC2, differentially regulates brain-derived neurotrophic factor (BDNF)-dependent dendritic spine development in CA1 and somatosensory neurons during the first postnatal week (Awad et al, 2018). This study suggests molecular mechanisms of dendritic spine formation in different brain regions might not be completely generalizable.…”
Section: Discussionmentioning
confidence: 99%